2021
DOI: 10.1016/j.bja.2021.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic properties of remimazolam in subjects with hepatic or renal impairment

Abstract: Background: Remimazolam is a new benzodiazepine for procedural sedation and general anaesthesia. The aim of this study was to characterise its pharmacokinetic properties and safety in renally and hepatically impaired subjects. Methods: Two separate trials were conducted in patients with hepatic (n¼11) or renal impairment (n¼11) compared with matched healthy subjects (n¼9 and n¼12, respectively). The hepatic impairment trial was an open-label adaptive 'Reduced Design' trial, using a single bolus of remimazolam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
98
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 14 publications
1
98
0
1
Order By: Relevance
“…22 A recent study showed that the pharmacokinetic properties of RT were not affected by hepatic impairment without dose adjustments. 23 Moreover, flumazenil is a specific antagonist of RT. 24 Our study showed that the mean times to RoC and extubation in group R were significantly shorter than that in group P. Compared with propofol, RT significantly shortened the PACU stay time.…”
Section: Discussionmentioning
confidence: 99%
“…22 A recent study showed that the pharmacokinetic properties of RT were not affected by hepatic impairment without dose adjustments. 23 Moreover, flumazenil is a specific antagonist of RT. 24 Our study showed that the mean times to RoC and extubation in group R were significantly shorter than that in group P. Compared with propofol, RT significantly shortened the PACU stay time.…”
Section: Discussionmentioning
confidence: 99%
“…25 In addition, remimazolam did not differ between elderly and younger patients or between patients with normal renal function and end-stage renal failure. 16 However, its use requires caution in patients with severe hepatic impairment, 26 which is why we excluded patients with abnormal liver function. We also excluded patients with opioid or alcohol abuse because mortality has been shown to be higher for certain categories of patients who use opioids for pain reduction or abuse drugs, such as opioids or alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with patients in the RT group, the EP group's onset time was significantly higher in (41 s vs 32 [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] s, p < 0.05; Table 3). However, there were no significant differences in the procedure time (p = 0.846) or cecal intubation time (p = 0.320) between the two groups (Table 3).…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…One important factor to consider is how the pharmacokinetic properties of remimazolam are altered in various populations, particularly in elderly patients and those with renal or hepatic impairment. The pharmacokinetic properties were not significantly different between the elderly (median age: 66.0 years) vs. young (median age: 21.0 years) patients [ 18 ], patients with normal renal function (estimated glomerular filtration rate [eGFR] ≥ 90 ml/min/1.73 m 2 ) vs. those with end-stage renal failure (eGFR < 15 ml/min/1.73 m 2 ), and patients with normal hepatic function vs. those with mild/moderate hepatic dysfunction (Child-Pugh class A and B) [ 19 ]. In contrast, the area under the concentration-time curve value from zero to infinity (AUC 0-inf ) was higher and clearance was lower in patients with severe hepatic impairment (Child-Pugh class C) than those in normal healthy volunteers (38.1%, both).…”
Section: Pharmacological Characteristicsmentioning
confidence: 99%
“…In contrast, the area under the concentration-time curve value from zero to infinity (AUC 0-inf ) was higher and clearance was lower in patients with severe hepatic impairment (Child-Pugh class C) than those in normal healthy volunteers (38.1%, both). Consequently, remimazolam exposure may be increased, and elimination may be prolonged in patients with severe hepatic impairment; therefore, careful dosage adjustment is recommended for these patients [ 19 ]. However, these pharmacokinetic analyses were performed using sparse data from small populations; hence, large-scale randomized controlled studies are needed to clarify the safety profile of remimazolam in the aforementioned populations.…”
Section: Pharmacological Characteristicsmentioning
confidence: 99%